The Implementation of Role Play Technique to Enhance EFL Students’ Speaking Skill - Fiani, Ani; Nahak, M Maria Ignasia (Journal of English Education, Literature and Linguistics, 2025)
Speaking remains an important but difficult skill for EFL learners due to the fear of being assessed and not having the opportunity for hands-on practice. In this study, 24 peer-reviewed articles from 2022–2025 were examined. The study employed a qualitative descriptive library research approach. Based on the findings, role-playing significantly enhanced students' confidence, vocabulary, pronunciation, and fluency by offering a secure and engaging setting. Furthermore, it reduces language anxiety and promotes imaginative and cooperative activities. It is primarily implemented through the use of structured group activities, reflective follow-up, and realistic scenarios. According to this study, role-playing enhances students' social and psychological growth as well as their language proficiency. Consequently, it is strongly advised that role play be used frequently in EFL classes.